Optimising prehospital trauma triage for older adults: challenges, limitations, and future directions - Harthi, Naif; Goodacre, Steve; Sampson, Fiona C. (Frontiers in Medicine, 2025)
The ageing population presents significant challenges for prehospital trauma care, with older adults experiencing higher rates of undertriage and overtriage due to age-related physiological changes, frailty, and polypharmacy. Standard trauma triage tools, primarily designed for younger populations, often fail to accurately assess injury severity in older adults, leading to delays in definitive care or unnecessary resource use. This narrative review synthesises current evidence on the limitations of existing trauma triage tools for older adults, highlighting challenges such as inconsistent implementation, paramedic training gaps, and age-related biases. The review explores the role of adjusted systolic blood pressure thresholds, frailty assessments, and geriatric-specific triage protocols in improving triage accuracy. While these modifications show promise, their integration into prehospital care remains limited due to logistical and clinical barriers. Key findings suggest that incorporating frailty assessments, refining age-specific triage criteria, and enhancing paramedic education can improve the precision of prehospital trauma triage for older adults. However, significant research gaps remain, including the need for large-scale prospective studies on geriatric-specific triage tools and investigations into the impact of triage modifications on long-term patient outcomes. Standardising geriatric triage protocols, leveraging digital decision-support tools, and addressing disparities in trauma centre access are critical to optimising prehospital care for older trauma patients. Future research should focus on refining triage strategies to enhance decision-making and ensure that older adults receive timely, appropriate trauma care, ultimately reducing preventable morbidity and improving patient outcomes.